How would mother's decision to work affect childbearing in Malaysia? - Evan, Lau; Siti Nur Zahara, Hamzah (Central and Eastern European Online Library, 2015)
The authors analyze the dynamics of fertility and its determinants with a particular focus on the role of female education and working decisions. The analysis is based on multivariate co-integration framework and out-of-sample variance decompositions. Results provide support that in the long run, fertility decline may be the consequence of a complex dynamic interaction with per capita or household income, while self-inflicted female decision to pursue studies and career development may influence fertility decline in the short run for Malaysia. It is evident that both ideational and structural hypothesis explaining fertility are important for understanding fertility decline in Malaysia.